Neurophysiological, metabolic and cellular compartments that drive neurovascular coupling and neuroimaging signals - Moreno, Andrea; Jego, Pierrick; de la Cruz, Feliberto; Canals, Santiago (Frontiers in Neuroenergetics, 2013)
Precise knowledge of the mechanisms that coordinate work and energy supply of the brain, the so called neurovascular coupling, is fundamental for the understanding of brain energetics, but also for the interpretation of brain imaging signals obtained in techniques such as functional magnetic resonance imaging (fMRI). Interactions between neuronal activity and cerebral blood flow regulation are largely compartmentalized. First, there exists a functional specialization where glutamatergic peri-synaptic activity and its electrophysiological events are linked to vascular responses. Second, the metabolic processes that fuel peri-synaptic activity are partially segregated between glycolytic and oxidative compartments. Finally, there is a cellular segregation between astrocytes and neurons, which has potentially important implications on neurovascular coupling. Experimental data is progressively showing a tight interaction between the products of energy consumption and neurotransmission-driven signaling molecules that regulate blood flow. Here, we review some of these issues in light of recent findings with special attention to the neuron-glia interplay on the generation of neuroimaging signals.